Financing Bologna, the internationally mobile students in European higher education - Marcel Gérard (Center for Economic Studies and ifo Institute (CESifo), 2008)
Despite the importance of the Bologna process for the mobility of students, and the further mobility of graduates, as well as for peace, growth and welfare in that area, nothing has been decided so far for the financing of internationally mobile students, so that the burden of that financing, usually public, is supported by the host country. Moreover in- and outflows of students show imbalances and such imbalances are expected to increase with mobility. Therefore, we first suggest and discuss an alternative system transferring the responsibility for financing higher education to the country of origin of the students (except for those from developing countries). Origin country finances students from its territory through a two-part portable voucher: one part is dedicated to the financing of the true cost of studies, the other part intends to support student's life and might be designed in such a way that some social goals are reached. Those vouchers can be used anywhere in a defined international area provided it is in the designed field of studies and in a school whose quality has been recognized by the issuing country. Some actual systems at work in the world, which prefigure aspects of the proposal, are presented in appendix. Second, we show that, when coupled with a compensation of the origin country in case of international career of the graduate, the system proposed in this paper might be equivalent to a centralized efficient design.
Keywords: H41; H77; I20; 330; Bologna process; higher education; mobility; federalism; subsidiarity; European Union; Studium; Auslandsaufenthalt; Studienfinanzierung; Finanzföderalismus; EU-Staaten